Trilaciclib prior to chemotherapy reduces the usage of supportive care interventions for chemotherapy‐induced myelosuppression in patients with small cell lung cancer: Pooled analysis of three randomized phase 2 trials. (18th August 2021) - Ferrarotto, Renata; Anderson, Ian; Medgyasszay, Balazs; García‐Campelo, Maria Rosario; Edenfield, William; Feinstein, Trevor M.; Johnson, Jennifer M.; Kalmadi, Sujith; Lammers, Philip E.; Sanchez‐Hernandez, Alfredo; Pritchett, Yili; Morris, Shannon R.; et al.
Abstract: Background: Supportive care interventions used to manage chemotherapy‐induced myelosuppression (CIM), including granulocyte colony‐stimulating factors (G‐CSFs), erythropoiesis‐stimulating agents (ESAs), and red blood cell (RBC) transfusions, are burdensome to patients and associated with greater costs to health care systems. We evaluated the utilization of supportive care interventions and their relationship with the myeloprotective agent, trilaciclib. Methods: Data were pooled from three independent randomized phase 2 clinical trials of trilaciclib or placebo administered prior to chemotherapy in patients with extensive‐stage small cell lung cancer (ES‐SCLC). The impact of supportive care on the duration of severe neutropenia (DSN), occurrence of severe neutropenia (SN), and occurrence of RBC transfusions on/after week 5 was analyzed across cycles 1–4. Concordance and association between grade 3/4 anemia, RBC transfusions on/after week 5, and ESA administration was also evaluated. Results: The use of G‐CSFs, ESAs, or RBC transfusions on/after week 5 was significantly lower among patients receiving trilaciclib versus placebo (28.5% vs. 56.3%, p < 0.0001; 3.3% vs. 11.8%, p = 0.0254; and 14.6% vs. 26.1%, p = 0.0252, respectively). Compared with placebo, trilaciclib significantly reduced DSN and SN, irrespective of G‐CSF administration. RBC transfusions and ESAs were most often administered in patients with grade 3/4 anemia; however, patients typically received RBC transfusions over ESA administration. Conclusions: By improving CIM and reducing the need for associated supportive care, trilaciclib has the potential to reduce the burden of myelosuppression on patients receiving myelosuppressive chemotherapy for the treatment of ES‐SCLC. Trial registration: ClinicalTrials.gov (NCT02499770; NCT03041311; NCT02514447). Abstract : Compared with placebo, administering trilaciclib prior to chemotherapy reduces chemotherapy‐induced neutropenia and anemia, with a reduction in the use of hematopoietic growth factors and red blood cell transfusions. By improving key myelosuppressive endpoints and reducing the need for associated supportive care, trilaciclib has the potential to reduce both the societal and economic burden of chemotherapy‐induced myelosuppression on patients with extensive‐stage small cell lung cancer.